Estimation of biofilm, proteinase & phospholipase production of the Candida species isolated from the oropharyngeal samples in HIV-infected patients - Lahkar, Vicky (Indian J Med Res, 2017)
BACKGROUND & OBJECTIVES: Candida, the most common opportunistic infection in acquired immunodeficiency syndrome (AIDS), attributes its pathogenicity to its virulence factors, mainly the biofilms, the proteinases and the phospholipases. There is a significant interplay of these factors during the HIV infection. This study was aimed to estimate the biofilm, proteinase and phospholipase production in Candida species isolated from the oropharyngeal samples in the HIV-infected patients. METHODS: A total of 126 consecutive HIV-positive patients were screened for Candida growth using oropharyngeal swabs. Identification was done by Gram staining, germ tube test, chlamydospore identification, chromagar and biochemical tests on Vitek 2. Biofilm production was observed on Sabouraud's dextrose broth with glucose, phospholipase production in egg yolk agar medium and proteinase production in bovine serum albumin agar medium. RESULTS: Of a total of 126 patients, 53 (42.06%) showed Candida growth: Candida albicans (n=46, 86.8%) was most common followed by the non-albicans Candida (NAC) (n=7, 13.93%). Of a total 33 (62.3%) biofilm positive isolates, significant production was observed in the NAC species (P <0.05). C. albicans reported the highest phospholipase (n=37/41, 90.24%) and proteinase (n=37/43, 86%) activities in a total of 41 (77%) phospholipase positive and 43 (81.1%) proteinase positive isolates. INTERPRETATION & CONCLUSIONS: Although C. albicans was the most common Candida species identified in HIV positive patients, the emergence of NAC was of special concern. Virulence factors such as biofilms, proteinases and phospholipases were noted in both these groups. Further research is required for better understanding of the pathogenic role of Candida species so as to aid in therapeutic interventions.